Nanonetwork-structured yolk-shell FeS2@C as high-performance cathode materials for Li-ion batteries. (December 2018) - Su, Quanfei; Lu, Yuheng; Liu, Shaohong; Zhang, Xingcai; Lin, Yanhuan; Fu, Ruowen; Wu, Dingcai
Abstract: Pyrite FeS2 is a promising alternative to typical intercalation cathodes for rechargeable lithium-ion batteries (LIBs) by virtue of its extremely high theoretical capacity. However, the inferior rate capability and fast capacity degradation caused by the sluggish reaction kinetics and large volume expansion upon lithiation greatly hinder its practical application. Herein, a chemical crosslinking strategy is developed for the synthesis of the yolk-shell pyrite FeS2 @porosity-rich sulfur-doped carbon nanonetworks (FeS2 @C NNs) as cathode materials for high-performance LIBs. The 3D nanonetwork structure constructed by tight covalent connection of carbon shells can act as highways to facilitate the electron transport kinetics, while the well-orchestrated internal cavities of the yolk-shell nanostructure provide large void space to accommodate the volume expansion of pyrite FeS2 . In addition, the porosity-rich characteristic of carbon shells ensures fast pathways for the Li + diffusion across the shells. As a result, the yolk-shell FeS2 @C nanonetworks exhibit excellent high-rate capability (353 mAh g −1 at 10 C) and exceptionally long lifespan of 1000 cycles with a high capacity of 435 mAh g −1 at a large current density of 5 C, which is by far the best of pyrite FeS2 -based cathodes for LIBs. Graphical abstract: Image 1